2023
DOI: 10.1186/s12981-023-00572-6
|View full text |Cite
|
Sign up to set email alerts
|

Current ART, determinants for virologic failure and implications for HIV drug resistance: an umbrella review

SeyedAhmad SeyedAlinaghi,
Amir Masoud Afsahi,
Ali Moradi
et al.

Abstract: Objective The purpose of this study is to investigate the incidence of determinants for virologic failure and to identify predisposing factors to enhance treatment efficacy. Tackling this global public health issue is the key to reducing the rate of virological failure and increasing the success of treatment for those living with HIV. Methods This umbrella review delves into various aspects of current anti-retroviral therapy (ART) which is the prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…That study demonstrated a high prevalence of the mutation, which was associated with poorer responses to efavirenz-based regimens, particularly in patients with high baseline VL (13). These findings underscore the importance of considering VL and resistance patterns at the onset of therapy (16).…”
Section: Discussionmentioning
confidence: 62%
“…That study demonstrated a high prevalence of the mutation, which was associated with poorer responses to efavirenz-based regimens, particularly in patients with high baseline VL (13). These findings underscore the importance of considering VL and resistance patterns at the onset of therapy (16).…”
Section: Discussionmentioning
confidence: 62%
“…These individuals are likely to be at higher risk of severe COVID-19 clinical outcomes due to their compromised immune status [ 6 ]. The presence of detectable viral loads has been associated with a younger age, a higher likelihood of missing medical appointments, and a lack of treatment adherence [ 34 ]. These factors could also partially explain why this important sub-population is under-vaccinated and underscores the necessity for comprehensive, patient-centered approaches to support PWH in achieving optimal health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, EBOV persistence and sequelae in animal models, and even humans, may hinge upon a therapeutic-dependent persistence mechanism [14,16,23] which is a risk we take with many viral infections for which we have approved treatments. The best example for this phenomenon is human immunodeficiency virus (HIV) for which many tretaments exist with known resistance mutations [24][25][26]. It was hypothesized that a mutation in the EBOV GP, specifically E545D [17], may be correlated with viral persistence, though other, currently unknown mutations may also be associated with viral persistence.…”
Section: What Is the Significance Of Ebov Persistence In Animal Models?mentioning
confidence: 99%